Perceived importance of e-journals and it's association with e-satisfaction among international postgraduate students in UTM - Lek, Hsiao Yen, 1985-; Mohd. Shoki Md. Ariff, supervisor; Fakulti Pengurusan dan Pembangunan Sumber Manusia (2010)
Thesis (Sarjana Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2010